Red-brown hardpan: distribution, origin and exploration implications for gold in the Yilgarn Craton of Western Australia - Mahizhnan, Annamalai (Curtin University, 2004)
Red-brown hardpan occurs extensively in Western Australia in the arid and semi-arid regions of the Murchison, Pilbara and Eastern Goldfields divisions, between longitudes 115ºE and 124ºE and latitudes 23ºs and 30ºs. It occupies an area of about 360,000 sq. km, two thirds of which occurs in the Yilgarn Craton. The purpose of this research is to map the distribution of red-brown hardpan in the Yilgarn Craton of Western Australia; study the relationship between landscape, soil texture and vegetation; investigate the physical characteristics, petrology, mineralogy, geochemistry and cementing agents; and thereby determine the processes invaded in forming red-brown hardpan. The relation of red-brown hardpan to gold is investigated and determined its implications in mineral exploration. The main case study areas were the Goldfields Gas Pipe Line, the Federal Open Pit Gold mines and the Menzies district in the Kalgoorlie-Menzies region of the Eastern Goldfields; areas in and around the Woolgorong Station in the Murchison Province and at the Wiluna Gold Mines in the Northeastern Goldfields. The findings and conclusions of this research are summarised below. Red-brown hardpan occurs at or near the land surface and may vary from less than one metre to more than 10 m thick. It is exclusively developed in colluvium and alluvium, showing varying stages of cementation ranging from weakly cemented through moderate to strongly cemented. In addition, calcrete and red-brown hardpan occurs together in many places, south of the Menzies line, and this distribution suggests that red-brown hardpan was once more extensive and has been subsequently replaced by carbonate to form calcareous red-brown hardpan and calcrete. Red- brown hardpan predominantly occurs in regions with Q50 mm annual rainfall.In present-day higher rainfall (400 to 500 mm) regions, red-brown hardpan is being weathered. There is no relationship between the distribution of mulga (Acacia aneura) and red-brown hardpan. Red-brown hardpan is exclusively developed in colluvium containing a minimum of 20% quartz, 15% clays and 2% iron oxides. It is bright reddish brown to reddish brown, earthy, with a sandy loam texture, blocky structure and porous. Red-brown hardpan is hard (up to 12 MPa), being characterised by sub-horizontal laminations predominantly of uncemented kaolinite. Ped surfaces may be coated by Mn oxide and carbonate which may be precipitated along the laminations. The mineralogy of the cement is complex. Data from XRD, SEM, TEM, EFTEM, FTIR and NIR investigations show poorly-ordered kaolinite and opal-A as the main components. Illuvial multilayered argillaceous cutans containing silica and alumina in a ratio of 2:l form the cement. Secondary silica (SiO2-95%) coatings are common, mainly as opal-A, on ped surfaces and on the inner walls of voids and vughs. Etch pits are developed in these coatings and some of them are filled by kaolinitic clays. Selective dissolution experiments using acid ammonium oxalate show that oxalate- soluble amorphous and poorly ordered silica and alumina in red-brown hardpan have molar ratios of about 1.6 to 2 A1203:SiO2.These results suggest that red-brown hardpans were formed where there was sufficient water during the wet season to dissolve alumina and silica, but insufficient to leach them. During the subsequent dry season, the dissolved alumina and silica was precipitated as poorly-ordered kaolinite and opal-A. Successive dissolution and precipitation led to fusion of poorly-ordered kaolinite and opal-A at a nanometre scale to progressively cement the colluvium. The age of the red-brown hardpans, estimated by paleomagnetic dating of hematite, is from Pleistocene to present. Based on the findings of this research, the red-brown hardpan is redefined and primarily classified on its degree of cementation as: (1) weakly cemented, (2) moderately cemented and (3) strongly cemented. It is further classified chemically into: (1) siliceous, (2) calcareous and (3) ferruginous. In the Yilgarn Craton, red-brown hardpan is believed to occur mainly north of the 'Menzies Line'. However, this study reveals the presence of red-brown hardpan 75- 150 km south of the Menzies Line and the new southern boundary is closer to latitude 29ºs. Geochemical investigation at the Federal Open Pit Gold mines, Broad Arrow, north of Kalgoorlie indicate that there are Au anomalies in red-brown hardpan. Gold concentration is up to 50 ppb against the background anomaly of 10 ppb. Sequential and partial extraction analyses show significant correlation of Au with Ag, Ca, Ce, Co, Mg, Mn and Ni. This suggests that the Au concentration in red-brown hardpan is due to: (a) mechanical dispersion due to reworking of Au-bearing clasts in the sediment and (b) hydromorphic dispersion from the underlying mineralisation. It can therefore be used as a useful sampling medium for gold exploration.